Pengaruh Motor Relearning Programme Terhadap Peningkatan Aktivitas Fungsional Pada Pasien Pasca Stroke Di Rumah Sakit Sari Asih Sangiang Tangerang - Hariandja, Andy Martahan Andreas; Sariana, Erna; Rahmadianti, Gisca (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
Background: Decreased functional activity is a frequent problem in post-stroke patients with 65.5% of them causing dependence on others in daily activities. Motor relearning programme is one of the intervention methods used to improve functional activity, but this intervention has not been widely used in several medical rehabilitation centers including at this research site. Aim: To determine the effect of motor relearning programme and conventional intervention on improving functional activity in post-stroke patients. Methods: This study used pre-experimental with one group pre-posttest. This study was conducted 2 times a week for 6 weeks. The sample of this study consisted of 12 people. Measurement of functional activity using the Barthel Index before and after intervention. Hypothesis testing used with normally distributed data is paired sample t-test. Results: The results of the effect test between before and after the intervention on functional activity get a p-value of 0.002 (<0.05) means there is an effect. The average result of functional activity obtained in pre test reached a value 75.67 and post test reached a value 90.5. Conclusion: There is a significant effect of motor relearning programme and conventional intervention on improving functional activity in post-stroke patients at Sari Asih Sangiang Tangerang Hospital.